17.3k views
5 votes
Solving Quadratic Equations: Factoring

Assignment Active
Solving a Quadratic Equation
Which statement is true about the equation (x - 4)(x + 2) = 16?
The equation X-4 = 16 can be used to solve for a solution of the given equation
The standard form of the equation is x2 - 2x - 8 = 0.
The factored form of the equation is (x + 4)(x - 6) = 0.
One solution of the equation is x = -6.

User Ruivo
by
6.0k points

1 Answer

1 vote

Answer:

The factored form of the equation is (x+4)(x-6)=0.

Explanation:

Because (x-4)(x+2)=x^2-4x+2x-8=16,

so that means x^2-2x-8=16,

move 16 to the other side,

you get x^2-2x-8-16=0,

simplify,

you get x^2-2x-24=0,

which satisfies (x+4)(x-6)=0 when factored out.

Because (x+4)(x-6)=x^2+4x-6x-24=x^2-2x-24=0.

User Slybloty
by
5.9k points